Tracking Responses to Items in Measures as a Means of Increasing Therapeutic Engagement in Clients: A Complementary Clinical Approach to Tracking Outcomes. (17th November 2014) - Cross, Simone; Mellor‐Clark, John; Macdonald, James
Abstract : This article presents a novel clinical application of questionnaire feedback, which focuses on change at the individual question level rather than the total mean or clinical score level. We term the approach 'Tracking Responses to Items in Measures' (TRIM) and promote the key aims to be (1) providing both client and practitioner with feedback on areas of positive change that may be masked by numerical feedback, (2) reinforcing client strengths and self‐efficacy, (3) exploring potential extra‐therapeutic factors that may contribute to the lack of change or deterioration on individual questions and (4) establishing a collaborative dialogue relating clients' problems to their goals and the consequent aims of treatment. This paper profiles the clinical origins and technical development of TRIM as a clear, user‐friendly display of item change across sessions using colour codes and illustrates the clinical utility through two clinical vignettes. Although the profile of the TRIM method herein uses the Clinical Outcomes in Routine Evaluation Outcome Measure, 1 we believe the method could easily be used with other measures. These could include Generalized Anxiety Disorder 7 and Patient Health Questionnaire 9 used in English National Health Service primary care Improving Access to Psychological Therapies services, or disorder specific measures for particular problems commonly used in National Health Service specialist services. We suggest TRIM is a practical complement to existing feedback systems, especially in work with clients who may be less likely to show empirically meaningful change on mean item or clinical score levels. Copyright © 2014 John Wiley & Sons, Ltd. Key Practitioner Message: Using outcome questionnaires as conversational tools helps practitioners focus on change at the individual item level rather than the numeric level. Tracking Responses to Items in Measures helps provide clients and practitioners with feedback on areas of positive change that may be masked by summary score analysis. Exploring the lack of change or deterioration on particular questions helps practitioners to assess extra‐therapeutic factors that may be compromising change. Using individual item change profiles as feedback for clients helps validate their progress and reinforce their strengths and self‐efficacy.